Generation Alpha: Challenges and Strategies of Teachers Based on Behavioristic Theory - Desvidisa Aryani, Niki; Marini, Arita; Edwita; Yatimah, Durotul; Zakiah, Linda (Jurnal Educative: Journal of Educational Studies, 2024)
The alpha generation is another term for children born in 2010 to 2025. The alpha generation is closely related to the use of technology products, especially gadgets. Therefore, this generation is also called the digital generation. Technology offers many benefits to humans, but technology can also create opportunities for students to exhibit deviant behavior. This is a special concern for teachers because it can affect the development and change of student behavior, especially basic education students. Therefore, teachers need to know what challenges and strategies can be applied in dealing with students from the alpha generation. Therefore, this study aims to identify challenges and strategies that can be applied by teachers in dealing with this generation of students based on behavioristic theory. This research is qualitative research with the method used is a literature study. Data is obtained from journals, articles, books and other documentation related to this topic. Based on the analysis of the results of the literature study, it was found that the challenges faced by teachers are related to mastery of technology and teachers' creativity in creating innovative and differentiated learning and becoming inspiring mentors for students. With this research, it is hoped that it can be knowledge for teachers in dealing with students at school based on its characteristics. So that the learning process and knowledge transfer can run well and achieve national education goals.